(untitled) (International Journal on Stereo & Immersive Media, 2022)
In this paper I make four interventions in favour of the seductive value of experiential media archaeology. 1) The constellation of material artefacts that mediate between us and the world are an implicit context for historic writing on perception, representation and epistemology. Engagement with the materiality of these often forgotten artefacts offers insight into the meanings of texts that exclusively text-based scholarship would otherwise miss. 2) Tacit, artisanal knowledge embedded in artefacts sometimes exceeds that which can be found in written texts. I argue that an effective way of accessing this material logic is to re-build old artefacts to see how they work. Applying the theory of extended cognition to this process, I make a case for its unique epistemological value. 3) I show how the seductive intimacy of these objects can be amplified by re-imagining their aesthetic possibilities. 4) I discuss the educational value of the “rational recreation” with media artifacts as “philosophical toys.”